Pengaruh Kepemimpinan dan Kompetensi Pegawai terhadap Kinerja Pegawai Pada Pusat Data dan Teknologi Informasi Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi - Handayani, Rima; Hermawati, Rahmi; Astuti , Eni Puji (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The purpose of this study was to determine the effect of leadership and employee competence on employee performance at the Pusat Data dan Teknologi Informasi Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi (Pusdatin Kemendikbudristek). The research method uses quantitative methods. The population in this study were all employees of the Pusat Data dan Teknologi Informasi Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi (Pusdatin Kemendikbudristek) totaling 179 people. The sampling technique used the Slovin formula with a sample size of 64 people. The data analysis method in this study uses the IBM SPSS version 26 application. Includes validity test, reliability test, classical assumption test, simple linear regression test, multiple linear regression test, coefficient of determination test, t test and f test. The results of this study are Leadership (X1) has a significant effect on Employee Performance (Y) with a determination value of 79.4% and in the hypothesis test obtained a tcount value of 14.371> t table 1.999 with a significance of 0.008 <0.05. Employee Competence (X2) has a significant effect on Employee Performance (Y) with a determination value of 63.2% and in the hypothesis test obtained a tcount value of 10.320> t table 1.999 with a significance of 0.006 <0.05. Leadership (X1) and Employee Competence (X2) simultaneously have a significant effect on Employee Performance (Y) with multiple linear regression equations Y = 4.193 + 0, 630X1 + 0.253X2. With a determination value of 43.1%. Hypothesis testing obtained Fcount value 117.553> Ftable 3.15 with a significant level of 0.000 <0.05, thus Ho1 is rejected and Ha1 is accepted, meaning that simultaneously Leadership and Employee Competence have a positive and significant effect on Employee Performance of the Pusat Data dan Teknologi Informasi Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi (Pusdatin Kemendikbudristek).